Application of nanoparticles in the treatment of acute lung injury: Current situation and future directions - Yan Zhang; Weiyao Sun; Min Wang; Yingying Qian; Qing Zheng; Wei Wang; Heyu Yang; Yansu Wang; Mingjing Zhou; Xianwen Wang; Chun Yang (Materials Today Bio)
Acute lung injury (ALI) and its severe form, acute respiratory distress syndrome (ARDS), are critical conditions characterized by disruption of the alveolar-capillary barrier, uncontrolled inflammation, and progressive hypoxemia, with mortality rates exceeding 40 %. While conventional therapies such as mechanical ventilation and glucocorticoids can partially alleviate symptoms, they face limitations, including low drug delivery efficiency, systemic toxicity, and inability to precisely regulate pathological microenvironments. Nanoparticles (NPs), which leverage their unique size effects, surface modifiability, and multifunctional integration capabilities, demonstrate advantages in targeted delivery, reduced systemic side effects, and multifunctional therapeutic potential and are emerging as novel tools to overcome current therapeutic bottlenecks. This review systematically summarizes the classification, mechanisms of action, and applications of NPs in ALI/ARDS treatment, while critically evaluating translational challenges and future development trajectories.